(untitled) - Watson, W. Petrie (London, 1904)
Contents: a spectacle of paradox, a fantasy of mystery, the metropolis of a revolution, Tokyo's automatic telephones,...
Keywords: Nhật Bản,Japan; Chính trị và pháp quyền,Politics and government